Implementation of zakat among Muslims in Ipoh: a study of Majlis Agama Islam Dan ‘Adat Melayu Perak (MAIPk) / Nurul Izzah Atirah Mohd Azan - Mohd Azan, Nurul Izzah Atirah (2021)
In Malaysia, there are still people who live in poverty to the point of being homeless because there is no source of income to survive adequately. So, in eradicating the poverty they have faced, each state has institutions to manage and distribute Zakat to those who need it. Also, Zakat is an obligation that must be fulfilled by all capable Muslims as commanded by Allah SWT. Not only that, but Zakat can purify hearts and property and produce the qualities of helping fellow Muslims to make progress. Later, the purpose of this study was to analyze the process of implementing and distributing Zakat to the asnaf group entrusted by the Majlis Agama Islam dan ‘Adat Melayu Perak (MAIPk) in Ipoh, Perak. Furthermore, this study was completed through interviews with MAIPk workers so that the data obtained is more detailed. So, the result of this study is that we will know that Zakat institutions play an important role in ensuring transparency in distributing Zakat to achieve the goals that Islam wants to achieve.